ON THE POSITION OF FOREIGN LITERARY CRITICS TO JADIDS’ LITERARY HERITAGE (Scientific journal of the Fergana State University, 2023)
The article gives informatien about the attitude of foreign scientists towards the representatives of XX century literature, especially to the literary heritage of Jadid literature, the translation of the writer’s works by the foreign scientists into English, German, French and a number of other foreign languages